Widespread Disruptions of White Matter in Familial Multiple Sclerosis: DTI and NODDI Study - Gharaylou, Zeinab; Sahraian, Mohammad Ali; Hadjighassem, Mahmoudreza; Kohanpour, Mohsen; Doosti, Rozita; Nahardani, Shima; Moghadasi, Abdorreza Naser (Frontiers in Neurology, 2021)
Diffusion tensor imaging (DTI) is a non-invasive, quantitative MRI technique that measures white matter (WM) integrity. Many brain dimensions are heritable chiefly white matter integrity measured with DTI. Family studies are valuable to provide insights into the interactive effects of non-environmental factors on MS. To examine the contribution of familial factors to the diffusion signals across WM microstructure, we performed DTI and calculated Neurite orientation dispersion plus density imaging (NODDI) diffusion parameters in two patient groups comprising familial and sporadic forms of multiple sclerosis and their unaffected relatives. We divided 111 subjects [49 males and 62 females: range (19–60)] into three groups conforming to their MS history. Familial MS group includes 30 participants (patients (n = 16), healthy relatives (n = 14). Sporadic group include 41 participants (patients (n = 10), healthy relatives (n = 31). Forty age-matched subjects with no history of MS in their families defined as controls groups. To study the white matter integrity, two methods employed one for calculating the mean of DTI, FA, and MD parameters on 18 tracts using TRACULA and the other for whole-brain voxel-based analysis using tract-based spatial statistics (TBSS) on NDI and ODI parameters derived from NODDI and DTI parameters. Voxel-based analysis showed considerable changes in FA, MD, NDI, and ODI in the familial group as compared with control groups, reflecting widespread impairment of white matter in this group. The analysis of eighteen tracts with TRACULA revealed increased MD and FA reduction in more tracts (left and right ILF, UNC, and SLFT, forceps major and minor) in familial MS patients versus control groups. There were no significant differences between the patient groups. We found no consequential changes in healthy relatives of both patient groups in voxel-based and tract analyses. Considering the multifactorial etiology of MS, familial studies are of great importance to clarify the effects of certain predisposing factors on demyelinating brain pathology.